Influência do tamanho médio de grão nas propriedades ferroicas de compósitos magnetoelétricos particulados - Viana, Diego Seiti Fukano (2016)
In the case of composites materials, which presents the magnetoelectric coupling, there are so many questions about the influence of the microstructure on the coupled and uncoupled properties. Thereby, this work proposes the study of the grain size influence, of ferroelectric and magnetic phases, on the magnetic, electric and coupled properties in particulate magnetoelectric composites. In order to study the relationship property/microstructure in volumetric magnetoelectric composites, it was necessary to prepare samples with different average grain sizes, ie, the phases having average grain size in the order of micrometers or nanometers. To perform this study it was used as magnetic phase the CoFe2O4 and, as the ferroelectric phase, the [0,675] Pb(Mg1/3Nb2/3)O3 – [0,325] PbTiO3, mixed in molar ratio 20/80 %, using techniques like micro ball milling (to reduce particle size) and high energy ball milling (to mixture the phases) during the powder syntheses, and Spark Plasma Sintering (SPS) to densify the bulk. Due the presence of secondary phases in sintered composites generated during the application of SPS, a processing protocol was created based on a post sintering thermal treatment, in PbO rich atmosphere, which allowed the reduction of secondary phases without, however, changing the average size of grain. These procedures resulted in composite material suitable for the investigations of the electrical, magnetic and magnetoelectric properties, considering the different microstructures obtained. The magnetoelectric composites showed the self-biased effect arising from the intrinsic strain generated in one phase over the other. It was observed the properties dependence, coupled or uncoupled, with average grain size of both phases. Furthermore, the magnetoelectric composites presented the selfbiased effect that appears due to intrinsic strain generated from one phase over the other. Moreover, the evolution of the magnetoelectric coefficient behavior as a function of temperature and applied magnetic field has been more dependent on the variation of the average grain size of the ferroelectric phase than the ferrimagnetic phase, which can be attributed to the largest amount of ferroelectric phase in the structure compound.